2019
DOI: 10.1039/c8na00412a
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced heterogeneities in the emission of upconverting nanoparticles at the submicron scale unfolded by hyperspectral microscopy

Abstract: Hyperspectral microscopy of upconverting nanoparticles in polydimethylsiloxane evidence emission heterogeneities, at the submicron scale, induced by agglomeration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 74 publications
(98 reference statements)
2
9
0
Order By: Relevance
“…It is worth mentioning that, for distances around 4.0 Å, there is a competition between the quadrupole−quadrupole and exchange (also known as Dexter's mechanism 79 ) interactions for dominance in the process of nonradiative energy transfer between Ln 3+ ions. 78,80,81 As recently demonstrated, 51 it is also important to characterize the upconversion emission at the submicron scale, due to the possibility of inhomogeneity in the emission spectra. This is particularly relevant in the optoelectronic field, as temperature gradients influence devices operation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning that, for distances around 4.0 Å, there is a competition between the quadrupole−quadrupole and exchange (also known as Dexter's mechanism 79 ) interactions for dominance in the process of nonradiative energy transfer between Ln 3+ ions. 78,80,81 As recently demonstrated, 51 it is also important to characterize the upconversion emission at the submicron scale, due to the possibility of inhomogeneity in the emission spectra. This is particularly relevant in the optoelectronic field, as temperature gradients influence devices operation.…”
Section: Resultsmentioning
confidence: 99%
“…A similar dependence of the R/G ratio on the collection area has been already observed for the emission of nanoparticles with diameter ∼20 nm doped with Yb 3+ /Er 3+ ions and dispersed in polydimethylsiloxane. 51 It was suggested that the dependence of the R/G ratio might be due to the dependence on the size of the nanoparticles or clusters of nanoparticles (surface/volume ratio). 82 Our results correlates well with this previous observation because the increase of the collection area in the spectrofluorometer corresponds to sample regions containing a high dispersion of particle sizes (in accordance with Figure S2d, SI) that are all contributing to the measured emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it displays a low-relative intensity band in the same region as that found for the absorption of the Au-particles ( Figure 3) and a more intense one in the red spectral region, that results from the light scattered by the fucoidan-AuNPs indicating the presence of fucoidan-AuNPs aggregates (Figure 8F, Figures S3 and S4). The larger dimension of those aggregates, when compared to STEM data (Figure 4), is due to the spatial resolution of the optical image, and we also note that the contribution of the guidance of the scattered photons from the particles for the larger bright spots cannot be excluded [37]. We note that some of those bright spots (marked with arrows in Figure 8H) are localized in the same coordinates of the plane in which was possible to detect the cells, suggesting the incorporation of the fucoidan-AuNPs in the MG-63 cells, that it is in line with the flow cytometry results.…”
Section: Dark Field Imaging Of Mg-63 Cells Incubated With Fucoidan-aunpsmentioning
confidence: 77%
“…[ 18 ] As a result, insight about environment‐specific optical behaviour as well as optical anisotropy at a single‐crystal or single‐particle level becomes accessible. [ 19–26 ] We previously performed single‐particle optical characterization of upconverting LiYF 4 microparticles via hyperspectral imaging to explore the spatial variability of their upconversion emission intensity. [ 19 ] Heterogeneous RE 3+ dopant distribution, a difference in the crystal field strength experienced by dopant ions occupying different crystallographic sites within the lattice of the microparticle, and uneven surface‐ligand coverage have been all suggested as tentative explanations for the observed intensity variation exhibited by the erbium and ytterbium co‐doped LiYF 4 (LiYF 4 :Yb 3+ /Er 3+ ) microparticles during hyperspectral imaging.…”
Section: Introductionmentioning
confidence: 99%